2020
DOI: 10.3390/plants9081049
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Diagnosis of Eucalyptus at the Factor-Specific Level Using Machine Learning and Compositional Methods

Abstract: Brazil is home to 30% of the world’s Eucalyptus trees. The seedlings are fertilized at plantation to support biomass production until canopy closure. Thereafter, fertilization is guided by state standards that may not apply at the local scale where myriads of growth factors interact. Our objective was to customize the nutrient diagnosis of young Eucalyptus trees down to factor-specific levels. We collected 1861 observations across eight clones, 48 soil types, and 148 locations in southern Brazil. Cutoff diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
0
19
0
2
Order By: Relevance
“…The size and diversity of the dataset and number of features selected in the model should be commensurate to avoid overfitting. The GPR, ANN and Random Forest were found to be useful ML models for small-size yet complex agronomic datasets [18,21,22,43]. Random Forests may return staircase response curves, while GPR and ANN may return smooth response curves.…”
Section: Machine Learningmentioning
confidence: 98%
See 1 more Smart Citation
“…The size and diversity of the dataset and number of features selected in the model should be commensurate to avoid overfitting. The GPR, ANN and Random Forest were found to be useful ML models for small-size yet complex agronomic datasets [18,21,22,43]. Random Forests may return staircase response curves, while GPR and ANN may return smooth response curves.…”
Section: Machine Learningmentioning
confidence: 98%
“…On the other hand, proportions show Dirichlet distribution, and are thus multiplicative (products). While clr and ilr variables can be used as features in ML models, the accuracy of ML models appears to be little influenced by nutrient expressions [43]. Using raw concentrations as features may be preferable, because log ratio computation does not permit missing values, unless imputed or replaced by 0.65 times the detection limit [47], if the number of missing values is relatively small in the dataset.…”
Section: Compositional Data Analysis (Coda)mentioning
confidence: 99%
“…We found that relating berry yield to nutrient composition of leaves and stems and other features collected in the same year resulted in the highest model accuracy where all yield-impacting features documented in the dataset were included in the model. There is thus a need for paradigm change toward factor-specific nutrient diagnosis and site-specific fertilizer recommendations supported by large and diversified datasets [35,54,55].…”
Section: Nutrient Standardsmentioning
confidence: 99%
“…Espécies do gênero Eucalyptus, são amplamente cultivadas no mundo. O Brasil é o maior produtor mundial, com 7,6 milhões de hectares plantados e áreas em constante expansão (Binkley et al, 2017;IBGE, 2019;Vahl de Paula et al, 2020).…”
Section: Introductionunclassified